2021
DOI: 10.1158/0008-5472.can-20-3941
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Signaling Activated by Cancer-Associated Fibroblasts Determines the Histological Signature of Lung Adenocarcinoma

Abstract: Invasive lung adenocarcinoma (LADC) can be classified histologically as lepidic, acinar, papillary, micropapillary, or solid. Most LADC tumors manifest several of these histological subtypes, with heterogeneity being related to therapeutic resistance. We report here that in immunodeficient mice, human LADC cells form tumors with distinct histological features, MUC5AC-expressing solid-type or cytokeratin 7 (CK7)-expressing acinar-type tumors, depending on the site of development, and that a solid-to-acinar tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…These CAFs significantly promote the infiltration of arginase+ N2 neutrophils and stimulate their expression of CXCL2, CXCR4, and MMP-9 [107]. Furthermore, it has been shown that CAFs mediate the activation of TGF-β/Smad3 signaling in tumor cells to induce IL-8 secretion and promote MPO + neutrophil migration in lung cancer [172]. These MPO + neutrophils have been reported to contribute to the tumor progression, through the support of angiogenesis.…”
Section: Mechanisms Regulating Pro-and Anti-angiogenic Activity Of Neutrophils In Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…These CAFs significantly promote the infiltration of arginase+ N2 neutrophils and stimulate their expression of CXCL2, CXCR4, and MMP-9 [107]. Furthermore, it has been shown that CAFs mediate the activation of TGF-β/Smad3 signaling in tumor cells to induce IL-8 secretion and promote MPO + neutrophil migration in lung cancer [172]. These MPO + neutrophils have been reported to contribute to the tumor progression, through the support of angiogenesis.…”
Section: Mechanisms Regulating Pro-and Anti-angiogenic Activity Of Neutrophils In Cancermentioning
confidence: 96%
“…These MPO + neutrophils have been reported to contribute to the tumor progression, through the support of angiogenesis. Additionally, by releasing MMP-9, these neutrophils were suggested to promote further activation of TGFβ in tumor microenvironment [172].…”
Section: Mechanisms Regulating Pro-and Anti-angiogenic Activity Of Neutrophils In Cancermentioning
confidence: 99%
“…Sato et al showed correlation between TGFβ secretion from CAFs and tumor heterogeneity in lung adenocarcinomas. TGFβ stimulated lung adenocarcinomas tumor plasticity into acinar type [51]. Hence, TGFβ mediates a certain role in cell-to-cell cross talk between tumor and tumor microenvironments.…”
Section: Tumor Stromamentioning
confidence: 94%
“…In a separate study, Sato et al . showed that TGF-β1 released by α-SMA + mouse CAF induced morphological changes and gene expression of the tumor cells, thus may contribute to the histological heterogeneity of lung adenocarcinoma (Sato et al 2021 ). With regard to the effect of CAF heterogeneity on the "methylome", Su et al .…”
Section: Tumor Fibrosismentioning
confidence: 99%